Common Pests and Pesticides used in High Value Crops: A Case Study on Some Selected Districts of Nepal - Koirala, Pramod; Tamrakar, Ananda Shova (Journal of Food Science and Technology Nepal, 2014)
This study was carried out in eight districts of Nepal to explore the pests, pesticides and other agro-chemicals used in high value crops viz. tea, coffee, honey and vegetables (tomato and brinjal). The study carried out districts for tea were Jhapa and Illam, whereas for vegetables Bara and Kavre. Similarly, honey was studied in Chitwan and Nawalparasi, whereas coffee in Gulmi and Lalitpur. The results revealed that different type of pests were found to be problematic in high value crops production. Loopers were the major pests in tea, borers in coffee, fruit fly in vegetables and mites in beekeeping. Different pesticides and some other agro-chemicals have been found to be used for pest management. Additionally, pesticide residues analysis for selected pesticides was carried out using GC-MS technique. The result of analysis showed that non of pesticides was found at the detection level of 0.7 parts per million. DOI: http://dx.doi.org/10.3126/jfstn.v7i0.10608 J. Food Sci. Technol. Nepal, Vol. 7 (64-69), 2012